Effect of different carotenoid-containing diets on the vitamin A levels and colour parameters in Iberian pigs' tissues: utility as biomarkers of traceability. - Álvarez, R; Vicario, I M; Meléndez-Martínez, a J; Alcalde, M J (Meat science, 2014)
Retinol and fat colour parameters in Iberian pigs fed on different carotenoid-containing diets were assessed. Thirty animals in two groups were considered: Iberian breed pigs fed on acorns and grass (Montanera) and on concentrate (Cebo). Carotenoids and retinoids were analysed in the diets and in plasma, liver and perirenal fat of the animals by HPLC and HPLC-MS. Retinol levels in plasma and fat were similar in Montanera and Cebo animals. The utility of retonids and colour parameters as traceability index was also explored. Retinoids in liver classified correctly 93% of the animals according to their diet L* and hab. CIELAB parameters of the perirenal fat discriminated correctly 78.6% of the animals according to their diet. L* values for the Montanera animals were significantly different (P<0.01) from those fed on concentrate. It can be claimed that the liver retinol profile and fat colour parameters can be useful for feeding traceability purposes in Iberian pigs breed in Montanera and Cebo.

Genetic transformation of selected mature cork oak (Quercus suber L.) trees. - Álvarez, R; Alonso, P; Cortizo, M; CELESTINO, C; HERNÁNDEZ, I; TORIBIO, M; Ordás, R J (Plant cell reports, 2004)
A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens strain AGL1. Evidence of stable transgene integration was obtained by PCR for the nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos were germinated and successfully transferred to soil.
Keywords: Agrobacterium; Cork oak; Fagaceae; Somatic embryogenesis; Tree genetic transformation